Representasi Tubuh Non-Ideal Perempuan Pada Brand Campaign Summersalt - Radyana Putri Denissa Soemarsono (Jurnal Ilmu Komunikasi, 2022)
Beauty myths cannot escape the existence of beauty standards created by the social environment and developed by products of popular culture. As a woman, looking beautiful and perfect means having an ideal appearance such as slim, white, smooth, and tall, as well as emphasizing femininity. However, few women can achieve this beauty myth. In the midst of these conditions body positivity was born as a social movement that seeks to call for self-acceptance. This movement is often present in the commercialization of the fashion industry, one of which is the Summersalt brand which is involved in producing swimwear. In terms of its popularity, Summersalt is quite bold by starting to highlight issues and social stigma about body beauty. Furthermore, this research was conducted to find out the representation of women's non-ideal bodies featured in the Summersalt campaign call entitled "The Summer of Self-Love" in the summer season of 2022. Researchers used a constructivist paradigm and a qualitative research method with a descriptive type. In addition, this study also uses Thwaites' textual analysis in interpreting the meaning of the text, in the form of narrative text (linguistics) through writing and sound, as well as image text (visual) through codes, symbols, signs, and gestures. The results of the study revealed that through the campaign "The Summer of Self-Love", Summersalt was able to present non-ideal body justice and equality to be represented as a form of celebration of body diversity and a shift in disability identity discourse. Apart from that, Summersalt also views her campaign movement as a place to call for self-love and body positivity in practices against the hegemony of body beauty.